(untitled) (Heritage, 2020)
The national and cultural identity of a nation is, among other things, established through the monumental heritage of a certain territory. For Serbs living in Kosovo and Metohija, monuments glorifying the glorious Serbian past (Serbian heroes, rulers, warrior feats) represent a link with the entire Serbian nation and hope for the possibility of survival in that part of Serbia. However, the significance and number of public art monuments in Kosovo and Metohija, as part of the cultural heritage of Serbs, has not been sufficiently researched so far. The exact number of public monuments in the north of Kosmet is unknown, there is no list of these works in the Institute for the Protection of Cultural Monuments of Serbia. A great number of those monuments is destroyed by Albanian extremists in their desire to destroy the features of the physical and spiritual existence of the Serbs in Kosovo and Metohija.